The pace and tempo of running in the analysis of the performances of the top hurdlers at the Оlympic games in Paris - Ogandzhanov A.L.; Samoylov G.V.; Salamatov M.B.; Tsyplenkova E.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the key kinematic features that contribute to the success of the world’s top male hurdlers in the 110m hurdles race, we conducted a thorough examination of the performances at the Paris Olympics. Methods and structure of the study. The examination of official records, the study of video footage of elite hurdlers in competition, and the application of statistical techniques are all part of the process. Results and conclusions. It has been discovered that in modern men’s short-distance hurdling, the athletes run at a rapid pace between the hurdles, with some of the top athletes even reaching a pace that is faster than that of highly skilled sprinters, reaching up to 5.3-5.5 steps per second. The limited distance between the hurdles and the high height of the hurdles force the athletes to achieve speed primarily through their pace of running steps, rather than through their length. The running style of the Olympic champion G. Holloway (USA) is characterized by the efficiency of his motor actions in terms of technical execution at the hurdle distance. As the athlete increases their speed and improves their competitive result, their pace of running steps also increases, resulting in a faster barrier step. In these circumstances, the athlete’s barrier step is perceived as a running step performed with a greater amplitude and a higher trajectory than a regular running step, while the entire distance is visually perceived as a single continuous movement.